Dry Herbarium Based on Local Wisdom to Improve Student Learning Outcomes - Salsabila, Nadya; Rahmasari, Sitti; Sholeh, Makherus (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
Learning outcomes are the abilities students gain during the learning process. Implementing learning is not always successful, sometimes some obstacles impact student learning outcomes resulting in no improvement. Thus, teachers must be able to use interesting learning media to maximize learning activities. One of the learning media that can be used is the Dry Herbarium media based on local wisdom in science learning. In this media, plant specimens that have the properties to be used as medicinal plants are dried, then the media can be used as a learning medium to help maximize learning. This research aims to describe the use of Dry Herbarium learning media based on local wisdom to improve student learning outcomes at MI Taman Pemuda Islam Keramat Banjarmasin. This research method uses quantitative methods with True Experimental research type and pretest-posttest control group design, the sampling technique used is purposive sampling, data collection through written tests, interviews, and documentation, and data analysis techniques using descriptive statistical analysis. The results of the research show that the results of class IV science learning at MI Taman Pemuda Islam Keramat Banjarmasin using the Dry Herbarium media based on local wisdom are in a good category with an average of 75.09. So it can be concluded that the use of Dry Herbarium media based on local wisdom can improve student learning outcomes in science learning.